Correction: Development of glycosynthases with broad glycan specificity for the efficient glyco-remodeling of antibodies. Issue 56 (2nd July 2018) - Shivatare, Sachin S.; Huang, Lin-Ya; Zeng, Yi-Fang; Liao, Jung-Yu; You, Tsai-Hong; Wang, Shi-Yun; Cheng, Ting; Chiu, Chih-Wei; Chao, Ping; Chen, Li-Tzu; Tsai, Tsung-I; Huang, Chiu-Chen; et al.
Abstract : Correction for 'Development of glycosynthases with broad glycan specificity for the efficient glyco-remodeling of antibodies' by Sachin S. Shivatare et al., Chem. Commun., 2018, 54, 6161–6164.